A SING TEDx TALKS TO IMPROVE STUDENTS’ SPEAKING ABILITY AT ENGLISH DEPARTEMENT OF IAIN PAREPARE - Lestari, Ayu; Arqam; Asni, Yulie (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2023)
TED is a series of informative, educational, inspiring and sometimes mind-blowing talks featuring 'Ideas Worth Spreading'. TED Talks is a digital platform that can be accessed by all people to get information or entertainment. TED Talks is a YouTube channel filled with motivational speeches. therefore this study aims to determine the improvement of students' speaking skills by using the TED Talks video in terms of Fluency at the 4th semester of English department students of IAIN Parepare.The design of this study uses the experimental method. The population of this research is 59 students in semester 4 consisting of 3 classes. The TED is a series of informative, educational, inspiring and sometimes mind-blowing talks featuring 'Ideas Worth Spreading'. TED Talks is a digital platform that can be accessed by all people to get information or entertainment. TED Talks is a YouTube channel filled with motivational speeches. therefore this study aims to determine the improvement of students' speaking skills by using the TED Talks video in terms of Fluency at the 4th semester of English department students of IAIN Parepare.The design of this study uses the experimental method. The population of this research is 59 students in semester 4 consisting of 3 classes. The sample in this study was class C semester 4th consisting of 15 students who were taken based on purposive sampling. The research design is one group pre-test and post-test design. In this study there were three stages, namely pre-test, treatment and post-test. The instrument used is a test. Calculation of data in this study using automatic data analysis in Microsoft Excel and manual data using formulas.The research results showed that using TED Talks as a medium for student learning can improve students' speaking ability in terms of fluency. This is evidenced t-test value on fluency (3.62), which is higher than the t-value table (1.761). This study concludes that students' speaking skills are better after receiving treatment than before being given treatment. So, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Keywords: TED Talks, Speaking Skill. sample in this study was class C semester 4th consisting of 15 students who were taken based on purposive sampling. The research design is one group pre-test and post-test design. In this study there were three stages, namely pre-test, treatment and post-test. The instrument used is a test. Calculation of data in this study using automatic data analysis in Microsoft Excel and manual data using formulas.The research results showed that using TED Talks as a medium for student learning can improve students' speaking ability in terms of fluency. This is evidenced t-test value on fluency (3.62), which is higher than the t-value table (1.761). This study concludes that students' speaking skills are better after receiving treatment than before being given treatment. So, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Keywords: TED Talks, Speaking Skill.